2004
DOI: 10.1038/sj.emboj.7600256
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of dynamic glycine receptor clustering by gephyrin

Abstract: Gephyrin is a bi-functional modular protein involved in molybdenum cofactor biosynthesis and in postsynaptic clustering of inhibitory glycine receptors (GlyRs). Here, we show that full-length gephyrin is a trimer and that its proteolysis in vitro causes the spontaneous dimerization of its C-terminal region (gephyrin-E), which binds a GlyR b-subunit-derived peptide with high and low affinity. The crystal structure of the tetra-domain gephyrin-E in complex with the b-peptide bound to domain IV indicates how memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
213
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(230 citation statements)
references
References 40 publications
16
213
1
Order By: Relevance
“…While the crystal structure of the G and E domains has been partially determined, the instability of full-length recombinant gephyrin in solution and the lack of information about the structure of the C-domain are major obstacles for elucidating gephyrin function and the mechanism of gephyrin auto-aggregation [13]. Current models posit either formation of hexameric gephyrin scaffolds, with 6 gephyrin molecules binding to 3 GlyR [18], or aggregation of gephyrin trimers, each of which is bound to one GlyR [13].…”
Section: Gephyrinmentioning
confidence: 99%
See 2 more Smart Citations
“…While the crystal structure of the G and E domains has been partially determined, the instability of full-length recombinant gephyrin in solution and the lack of information about the structure of the C-domain are major obstacles for elucidating gephyrin function and the mechanism of gephyrin auto-aggregation [13]. Current models posit either formation of hexameric gephyrin scaffolds, with 6 gephyrin molecules binding to 3 GlyR [18], or aggregation of gephyrin trimers, each of which is bound to one GlyR [13].…”
Section: Gephyrinmentioning
confidence: 99%
“…These models of gephyrin aggregation are based on partial structural information, localization of the GlyR binding site in the E-domain, and identification of surface-exposed loops regulating gephyrin postsynaptic aggregation [13,24,18]. Although available experimental evidence does not allow distinguishing between them, an important outcome of gephyrin structure is its enzymatic activity, which requires the active sites on the G and the E domains to be in close spatial proximity.…”
Section: Gephyrinmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial cross-linking studies using puriWed spinal cord GlyR suggested that the receptor forms a pentamer with a deduced stoichiometry of three and two subunits and that the subunit was not involved in ligand binding (Langosch et al 1988;Laube et al 2002). Through its long intracellular loop between TM3 and TM4, the subunit can bind to gephyrin (Kim et al 2006;Meyer et al 1995;Sola et al 2004), thereby enabling the formation GlyR aggregations linked to subsynaptic protein scaVolds. However, the gephyrin scaVold (see below) is believed to provide three binding sites for GlyR subunits (Schrader et al 2004).…”
Section: Postsynaptic Membrane Specializationmentioning
confidence: 99%
“…Although the structure of the G-domain resembles that MogA, the path of its C-terminal ends suggests that the central and E-domains, which were both missing in the truncated polypeptide analyzed in the referring publication, should follow a similar 3-fold arrangement as the Gdomain. Although full-length gephyrin was shown to form a trimer, in vitro proteolysis causes spontaneous dimerization of its E-domain (Lardi-Studler et al 2007;Sola et al 2004). As the G-domain forms trimers and the E-domain can form dimers, it is believed that gephyrin is able to form a hexagonal scaVold in vivo (Fig.…”
Section: Analysis Of Gephyrin Dewcient Micementioning
confidence: 99%